Implementasi Undang-Undang No. UU 32 Tahun 2004 (Kasus Implementasi Lembaga Lokal di Riau) - Sujianto Sujianto (Universitas Riau, 2010)
Indonesia has the compound community, his complexity can be seen from twocharacteristics of the vertical complexity like; the layer economical social and politicalsocial and social culture. The complexity horizontally is to be based on associationrelations primodial. Henceforth this grouping forms a social organization formal andinformal. The two characteristics are very much seen in the ethnic group's Originalcommunity like the Sakai Ethnic Group and Akit. The two groups enter the transitioncurrent culture (food producing and tribe society). In a manner the culture the twocommunities have the typical characteristics, but the No. UU taking effect 5 in 1979happen the contraction even the abolition of the local culture culturally. During 1998reform brings the fresh wind is current him come back the local culture that is based withNo. UU 32 in 2004. His question how the implementation of this UU, because some ofthe authorized side the tradition already am not available. The aim of this article is to seethe implementation of this UU by using the structural theory functional, through fourfunctions that force. The implementation term is replaced with the implementation, tobring discussions in this article close. This study method uses the approach qualitativeand quantitative. The qualitative data is received through the interview and observation,afterwards changed with the Likert Scale to make the data to be quantitative. Theresearch result show that implementation of UU No.32 in 2004changed local institute,local structural and local cultural at implementation rural development.